(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study examines the role of international standards in English language teaching (ELT) and evaluation. It explores current trends, innovative methodologies, and difficulties educators face worldwide. The article highlights frameworks such as CEFR and IELTS in enhancing teaching quality and assessment accuracy, and offers guidance for incorporating these global standards into local educational practices.